Bahasa arab dan karakter bangsa: Mengintegrasikan nilai-nilai islam dalam pendidikan bahasa - Mafula, Siti Rofi'atul (Maliki Interdisciplinary Journal, 2025)
In addition to being a means of communication, Arabic is also a key to understanding the primary sources of Islamic teachings. In the realm of education, teaching Arabic in connection with Islamic values can shape a character rooted in strong morality and spirituality. This article explores how methods of Arabic language instruction based on Islamic values can be effectively applied in the curriculum, thereby building a generation that is not only proficient in the language but also possesses good character. The article also discusses the importance of integrating Islamic values into Arabic education as an effort to strengthen the nation's character. Moreover, it highlights that learning Arabic is not only about mastering the language, but also about introducing the moral values embedded in Islamic teachings. With this value-based approach, students can understand how values such as honesty, responsibility, and respect can be applied in daily life. Furthermore, Arabic education that is integrated with religious values can foster a sense of pride in Islamic culture and the Qur'anic language, which in turn can strengthen personal identity and solid moral character in the younger generation. Based on theoretical studies and several case studies, this article concludes that teaching Arabic that emphasizes religious values can be an effective way to shape a strong, moral nation and create a generation with good character.